2007
DOI: 10.1007/s00705-007-0976-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Brazilian strains of porcine circovirus type 2 (PCV-2) revealed by analysis of the cap gene (ORF-2)

Abstract: Porcine circovirus 2 (PCV-2) is associated with a broad range of syndromes. In this study, 19 of 870 samples from pigs from different Brazilian states were found to be positive for PCV-2 by polymerase chain reaction (PCR). A fragment of 700 nt of the cap gene (ORF-2) from the 19 PCV-2-positive samples were sequenced using three pairs of primers (Fa/Ra, Fb/Rb and Fc/Rc). Maximum parsimony genealogy with a heuristic algorithm using the 19 field strain studied here, 21 sequences from GenBank and PCV-1 as an out-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Porcine circovirus type 2 (PCV2) could be divided into two major genotypes based on sequencing analysis, but different nomenclature has been used, which are group 1 and 2, I and II, pattern 321 and 422, SG3 and SG1/SG2, A and B [8,[18][19][20]. Recently, Segale 0 s et al proposed that a standardized name for these genotypes, which were PCV 2a and 2b [11].…”
Section: Discussionmentioning
confidence: 99%
“…Porcine circovirus type 2 (PCV2) could be divided into two major genotypes based on sequencing analysis, but different nomenclature has been used, which are group 1 and 2, I and II, pattern 321 and 422, SG3 and SG1/SG2, A and B [8,[18][19][20]. Recently, Segale 0 s et al proposed that a standardized name for these genotypes, which were PCV 2a and 2b [11].…”
Section: Discussionmentioning
confidence: 99%
“…Despite most sequencing studies did not find any relation between PCV2 sequences and the occurrence of the disease (Larochelle et al, 2002;Pogranichniy et al, 2002;Larochelle et al, 2003;de Boisseson et al, 2004;Grierson et al, 2004;Wen et al, 2005;Martins Gomes de Castro et al, 2007), some recent studies and field observations (Timmusk et al, 2005;Opriessnig et al, 2006;Cheung et al, 2007aCheung et al, , 2007bStevenson et al, 2007;Woodbine et al, 2007) have suggested the opposite. Moreover, epidemiological Danish and British studies strongly suggested that the spread of porcine circovirus diseases (PCVDs) is consistent with the introduction of a "new infectious agent" or a "new strain" of a known agent into a naïve population (Vigre et al, 2005;Woodbine et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, their nomenclature has become ‘research group-dependent’. Thus, genotypes ‘1’ and ‘2’ from Grau-Roma and others (2008) correspond, respectively, to groups ‘1’ and ‘2’ (Olvera and others 2007), ‘I’ and ‘II’ (De Boisséson and others 2004), ‘ sg3 ’ and ‘ g1/sg2 ’ (Timmusk and others 2008), ‘A’ and ‘B’ (Martins Gomes de Castro and others 2007), ‘b’ and ‘a’ (Gagnon and others 2007) and restriction fragment length polymorphism patterns ‘321’ and ‘422’ (Carman and others 2008). Therefore, in order to counteract the current scientific confusion on genotype names, the members of the eu consortium on porcine circovirus diseases (www.pcvd.org) propose a standardised nomenclature for pcv-2 genotypes.…”
mentioning
confidence: 99%